Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 530 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Piranga flava hepatica Swainson, 1827", "Country is Mexico" ] } The dataset includes 530 records from 26 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0007353-160526112335914/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences